Challenges in Land Use Permits in Developing Tourism Areas in Rote Ndao Regency - Ade Pratiwi Hamid Koso; Ixora Lundia Suwaryono (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to evaluate the policy of publishing the Suitability of Spatial Utilization Activities in the developing tourism area in Rote Ndao Regency and identify the challenges faced. The study uses a descriptive qualitative approach through in-depth interviews, observations, and document studies. The analysis is carried out using William N. Dunn's Policy Evaluation Theory which includes indicators of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. The results show that the policy for issuing the Suitability of Spatial Utilization Activities has not fully answered the purpose of the policy, namely in facilitating the licensing process in accordance with spatial utilization, in this case the ease of the licensing process in accordance with the direction of spatial utilization and the development of sustainable tourism activities in Rote Ndao Regency. The main obstacles faced include the unavailability of Spatial Detailed Plan documents in the area which are integrated with the Online Single Submission system, regulatory limitations related to the utilization of coastal border areas to support tourism activities and the lack of optimal control and supervision activities after the issuance of permits, although the existence of tourism activities has had a positive impact on economic growth. This study recommends accelerating the preparation of Detailed Spatial Planning and Zoning Regulations in tourism areas, increasing human resource capacity, increasing coordination, synergy and data integration to realize sustainable spatial utilization and create a conducive climate for investment activities.